Interrelationship of Yield and Quality Attributing Traits in JNPT Lines of Rice - Choudhary, Pratibha; Mishra, D. K.; Koutu, G.K.; Pachori, Amita; Singh, S. K. (International Journal of Bio-resource and Stress Management, 2018)
In present study, one hundred eighty five JNPT (Jawahar New Plant Type) lines including five checks were evaluated for twenty eight morphological and quality traits planted in Randomized Complete Block Design with three replications. The experiment was conducted during kharif seasons of 2014 and 2015 at Seed Breeding Farm, Department of Plant Breeding and Genetics, College of Agriculture, JNKVV, Jabalpur (M.P.), India. Observations were recorded on the basis of middle five random competitive plants selected from each line in every replication for yield and quality traits. Considerable genetic variability was exhibited by all the yield and quality traits under study. It was observed that for selecting the high yielding lines in the rice the characters viz., spikelet density, fertile spikelets panicle-1, number of spikelets per panicle, panicle weight plant-1 and biological yield plant-1 might be considered. On the basis of high PC score in principal component analysis 10 most prominent JNPT lines JNPT 813, JNPT 811, JNPT 845, JNPT 770, JNPT 779, JNPT 777, JNPT 778, JNPT 749, JNPT 781 and JNPT(S) 10H were identified. Thus, these JNPT lines will be utilized as inbred for production of hybrid rice, with higher yield and better quality. However, after evaluation under different agro-ecological rice growing situations, these lines might be released as high yielding variety with better quality.